Cardiac angiosarcoma in a female adolescent: a case report - Wlisses Ramon Oliveira; Carla Pérez Machado; Marcelo Mendes Las Casas Moreira; Elisa Carvalho de Siqueira; Fabrício Tinôco Alvim de Souza; Fabiano Franco Monteiro Prado; Maria Carolina Barbosa Álvares; Paulo Ramos Botelho Antunes; Cláudia Souza Freitas Faleiro (BMC, 2019)
Abstract We report a rare case of cardiac angiosarcoma in a female adolescent patient that is an unusual case of cardiac angiosarcoma. As the initial symptoms are nonspecific our case demonstrated difficulty to establish the correct diagnosis. Our patient has in addition to these, malaise, diarrhea and hemoptysis which was mistakenly diagnosed with pneumonia. Here, we discuss aspects of computed tomography with a definitive diagnosis confirmed by immunohistochemistry, through a transthoracic radioguided biopsy. The patient presented improvement after urgent chemotherapy, however, she died 4 months after initial symptoms. In view of these aspects, it is clear the need for early diagnosis and a definition of optimized treatment in order to extend the survival of these patients.